PEMANFAATAN GOOGLE SITES UNTUK PUBLIKASI WEBGIS INFORMASI KETAHANAN PANGAN PETERNAKAN IKAN AIR TAWAR - Yuntari Purbasari; Khana Wijaya; Phinton Panglipur; Suhartini Suhartini; Akhmad Sayuti (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
The utilization of web-based Geographic Information System (WebGIS) technology is a strategic solution for presenting and publishing spatial data interactively. However, the development of WebGIS generally requires high costs and advanced technical expertise, which are not always available, particularly in regions with limited information technology resources. This study aims to design and implement a simple WebGIS using the Google Sites platform as a medium for publishing food security information in the freshwater fish farming sector in Prabumulih City. The system development method employed in this study is the Waterfall method, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. The research data include spatial data on the locations of freshwater fish farmers and attribute data related to production potential, which are presented in the form of interactive thematic maps. The results indicate that Google Sites is effective as a medium for publishing simple WebGIS due to its ease of access, free usage, and minimal requirement for advanced programming skills. The developed WebGIS is capable of presenting interactive information on the locations and production potential of freshwater fish farming, thereby enhancing data transparency and facilitating information access for local governments and the community. Therefore, the use of Google Sites as a WebGIS publication medium can serve as an economical alternative solution to support the strengthening of local food security in Prabumulih City.